A Qualitative Study of the Experiences and Factors That Led Physicians to Be Lifelong Health Advocates. (October 2016) - Law, Marcus; Leung, Pearl; Veinot, Paula; Miller, Daniel; Mylopoulos, Maria
Abstract : Purpose: Given the public's trust and the opportunities to observe and address social determinants of health, physicians are well suited to be health advocates, a key role in the CanMEDS physician competency framework. As some physicians find it difficult to fulfill this role, the authors explored the experiences and influences that led established physicians to be health advocates. Method: The authors used a phenomenological approach to explore this topic. From March to August 2014, they interviewed 15 established physician health advocates, using a broad definition of health advocacy—that it extends beyond individual patient advocacy to address the root causes of systemic differences in health. Interviews were audio recorded and transcribed verbatim. The transcripts were coded and the data categorized into clusters of meaning, then into themes. Data analysis was conducted iteratively, with data collection continuing until no new information was gathered. Results: Participants described the factors that contributed to the development of their health advocate identity (i.e., exposure to social injustice, upbringing, schooling, specific formative experiences) and those that facilitated their engagement in health advocacy work (i.e., mentors, training, systemic and organizational supports). They also highlighted how they continue in their role as lifelong advocates (i.e., continuous learning and improvement, self-reflection and self-reflexivity, collaboration, intrinsic satisfaction in the work). Conclusions: Many factors allow physician health advocates to establish and sustain a commitment to improve the health of their patients and the broader population. Medical schools could use these findings to guide curriculum development related to teaching this physician competency.